Theoretical Study of Cyclohexane -1,2-Diamine-Oxalate- Platinum Metal Complex and Comparing with Experimental Data: DFT Calculations - Shakir D. Al-Saeedi; Hamid Ibrahim Abbood; Wisam ShareefIrzooqi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Theoretical studies for calculating the molecular structure and electronic properties of Cyclohexane-1,2-diamine-oxalate- platinum metal complex by using density functional theory (DFT) for get electronicproperties and time dependent density functional theory (TD-DFT) for get excited state with B3LYP-SDDbasis sets at the Gaussian 09 of programs. The electronic states of the system have been calculated dependon Koopmans’ theorem.The results showed that the excitation energies of oxaliplatinum lie in the UV region of electromagneticradiation with very high biological reactivity, where The absorption spectra of complex recorded withwavelength (344.69nm), oscillator strength (0.0002). From calculations of the HOMO - LUMO energies,energy gap, hardness and softness, all this results showed oxaliplatinum are more soft and can easily interactwith enzymes because the enzymes are big soft molecules. Thus, the optimized geometry shows a goodagreement with the experimental results.